A three-dimensional human walking model. (24th November 2015) - Yang, Q.S.; Qin, J.W.; Law, S.S.
Abstract: A three-dimensional human bipedal walking model with compliant legs is presented in this paper. The legs are modeled with time-variant dampers, and the model is able to characterize the gait pattern of an individual using a minimal set of parameters. Feedback control, for both the forward and lateral movements, is implemented to regulate the walking performance of the pedestrian. The model provides an improvement over classic invert pendulum models. Numerical studies were undertaken to investigate the effects of leg stiffness and attack angle. Simulation results show that when walking at a given speed, increasing the leg stiffness with a constant attack angle results in a longer step length, a higher step frequency, a faster walking speed and an increase in both the peak vertical and lateral ground reaction forces. Increasing the attack angle with a constant leg stiffness results in a higher step frequency, a decrease in the step length, an increase in the total energy of the system and a decrease in both the peak vertical and lateral ground reaction forces. Highlights: A three-dimensional bipedal walking model with compliant legs is presented. The feedback control is proposed to regulate the walking performance. The leg stiffness and attack angle effects are investigated in the numerical studies.